Business model innovation in cultural and creative industries: Insights from three leading mobile gaming firms. (April 2020) - Landoni, Paolo; Dell'era, Claudio; Frattini, Federico; Messeni Petruzzelli, Antonio; Verganti, Roberto; Manelli, Luca
Abstract: This paper contains an exploratory analysis of the business model innovations (BMIs) that firms in cultural and creative industries (CCIs) undertake along their life-cycle. Despite the role that creative and cultural and creative firms (CCFs) have in the economic development of industrialised countries, they tend to remain small and often fail due to industry-specific constraints and tensions, such as the lack of managerial capabilities and complexity in nurturing value chain relationships. However, there has been relatively limited scholarly interest into the specific conditions and processes that enabled CCFs to overcome these liabilities, and in particular into the identification of the business models they have adopted along their life-cycle. In this paper, this issue is analysed by using the concept of BMI, which sheds light on how the reconfiguration of the activity system through which a CCF creates, delivers and captures value enables the exploitation of entrepreneurial opportunities over time. This paper builds on an in-depth historical study of three leading firms operating in the mobile gaming industry, namely Rovio, Zynga and King Digital Entertainment. Three main results emerge from this study. First, in the ramp-up phase of their life-cycle, CCFs organize their resource architecture to build a strong and recognized reputation. Second, in the development phase, BMI is used to leverage new distribution paradigms. Finally, in the maturity phase, firms dedicate resources to innovate their product portfolios by providing platforms that support the development and testing of new creative ideas and solutions. Findings and implications are then discussed. Highlights: Creative and Cultural Firms (CCF) can overcome resource constraints through business model innovation. Different constraints appear at different firm life-cycle stages: Ramp-up, Development and Maturity. In the ramp-up phase of their life-cycle, CCFs organize their resource architecture to build a strong and recognized reputation. In the development phase, BMI is used to leverage new distribution paradigms. In the maturity phase, platforms are created to support the development and testing of new creative ideas and solutions.